Interfacially Super‐Assembled Benzimidazole Derivative‐Based Mesoporous Silica Nanoprobe for Sensitive Copper (II) Detection and Biosensing in Living Cells. Issue 6 (22nd December 2021) - Xing, Chenchen; Deng, Jianlin; Fu, Wenlong; Li, Jichao; Xu, Lijie; Sun, Ruihao; Wang, Dan; Li, Chengwen; Liang, Kang; Gao, Meng; Kong, Biao
Abstract: Mesoporous silica nanoparticles (MSNs) functionalized with benzimidazole‐derived fluorescent molecules (DHBM) are fabricated via a feasible interfacial superassembly strategy for the highly sensitive and selective detection of Cu 2+ . DHBM‐MSN exhibits an obvious quenching effect on Cu 2+ in aqueous solutions, and the detection limit can be as low as 7.69×10 −8 M. The DHBM‐MSN solid‐state sensor has good recyclability, and the silica framework can simultaneously improve the photostability of DHBM. Two mesoporous silica nanoparticles with different morphologies were specially designed to verify that nanocarriers with different morphologies do not affect the specific detectionability. The detection mechanism of the fluorescent probe was systematically elucidated by combining experimental results and density function theory calculations. Moreover, the detection system was successfully applied to detect Cu 2+ in bovine serum, juice, and live cells. These results indicate that the DHBM‐MSN fluorescent sensor holds great potential in practical and biomedical applications. Abstract : A unique mesoporous silica nanoprobe (DHBM‐MSN ) based on benzimidazole derivative is constructed for the highly sensitive and selective detection of Cu 2+ . The designed DHBM‐MSN has obvious quenching effect on Cu 2+ in aqueous solution with extremely low detection limit. The detection system is successfully applied to detect Cu 2+ in bovine serum, juice and live cells. The results indicate that DHBM‐MSN fluorescent sensor holds great potential in practical and biomedical applications.